Peran Budaya dalam Perubahan Penggunaan Lahan di Permukiman Adat Kasepuhan Ciptagelar Sukabumi - Sahebat Noviyanto Saputro; Bambang Hari Wibisono (Jurnal Lanskap Indonesia, 2023)
Kasepuhan Ciptagelar has unique customs and culture that are still maintained today and does not close itself from the development of the times, but accepts it consciously. Over time, traditional settlements are faced with challenges to be able to meet their needs. This can change land use in this traditional settlement. This study aims to determine changes in land use and its relation to cultural factors. This research uses qualitative methods. The research was conducted in Kasepuhan Ciptagelar traditional settlement area between of 2001 to 2022. The research was carried out by reconstructing land use maps in Kasepuhan Ciptagelar which then identified changes from year to year. Furthermore, an analysis of the cultural factor in influencing land use changes in these settlements is carried out. The results of the analysis shows that during the research period there has been a continuous land use change. Cultural factors also influence the land use changes. The ngalalakon tradition became a major factor in the early period of settlement development. The perspective of accepting changes of era by the Ciptagelar community can be interpreted as an adaptation of settlements to keep up with the times and this perspective also makes continuous changes to Kasepuhan Ciptagelar.